THE IMPACT OF MEDIATED INSTRUCTION OF TEXT (MIT) STRATEGY IN TEACHING READING SKILL TO THE STUDENTS OF SMP NEGERI 13 BANDA ACEH - Sariakin Sariakin; Maulizan ZA (Jurnal Sosial Humaniora Sigli, 2021)
The aim of the research to find out if the use of Mediated Instruction of Text (MIT) strategy in reading skill can improve the eight grade students’ ability of SMP Negeri 13 Banda Aceh in mastering reading skill. This research is conducted by using pre-experiment with one class; pre-test and post-test design.  The population of this research is the eight grade students of SMP Negeri 13 Banda Aceh.  The total population of this study is 121 students who are composed of five classes; VIII1, VIII2, VIII3, and VIII4. Every class consists of about 30 students. Since the population was rather big thus writer takes  sample for this study. The sample of this research was class VIII1 at second grade of SMP Negeri 13 Banda Aceh. The class consisted of 30 students. The researcher used purposive sampling technique in choosing sample. The researcher chooses the students of class VIII1 because the students’ ability of the class is better than the other classes.  The data are taken through test.  The data gotten are analyzed by using gain score (GS). The result of this research shows that Gain Score (GS) score is 0.24.  It means there is a difference between the students’ ability in mastering reading skill before and after they are taught by using MIT strategy and the difference is 0.24 points or 24%. Therefore, the students’ ability in mastering reading skill increases 0.24 points or 24% after they are taught by using MIT strategy. Based on the result of the study, the English teachers of SMP Negeri 13 Banda Aceh should use MIT strategy in teaching reading skill because it can increase the students' ability in mastering reading skill.Key Words: Impact, Mediated Instruction of Text Strategy, Reading Skill